Implementasi Mandat Rasul Paulus di Kitab Galatia 3:1-14 Pada Tindakan Diakonia dan Nilai Kontribusinya bagi Umat Gereja-Gereja di Masa Pandemi Covid–19 - Elfrida Nababan (Areopagus : Jurnal Pendidikan Dan Teologi Kristen, 2021)
Abstract:This study aims to find out how the implications of justification by faith based on the letter Galatians 3:1-14 on the Acts of Diakonia and the Value of their Contributions to the People of the Churches during the Covid-19 Pandemic. This research is a theological study using the method of critical exegesis or interpretation of the text of the Bible. The research method used is a qualitative research method with an exegesis approach. Based on the results of exegesis, Paul asserted that faith is belief in Jesus Christ. Humans get justification or salvation from God because of God's mercy and God's grace to humans through Jesus Christ. Faith in Christ the True Gospel will enable man to gain God's salvation or justification. So that people who have faith get blessings from God.Based on the results of the study, it can be concluded that there is a very large positive impact in the church's Diakonia service to the congregation so that it has made growth in quantity and quality to date. Which is rooted in the Diakonia ministry which is carried out with household visits to sick congregations, grieving congregations and congregations who have problems in their families. The implication is that if church services, especially Diakonia, are carried out properly, they will produce good quality, quantity and organic congregations. And the church will have a congregation that fears God and is obedient to God's Word.Keywords: apostle paul's mandate, diakonia's actions, contribution to the peopleAbstrak:Penelitian ini bertujuan untuk mengetahui bagaimana implikasi pembenaran oleh iman berdasarkan surat Galatia 3:1-14 pada Tindakan Diakonia dan Nilai Kontribusinya Bagi Umat Gereja-gereja dimasa Pandemi Covid-19. Penelitian ini merupakan sebuah studi teologis dengan menggunakan metode critical exegesis atau penafsiran teks Kitab Suci. Metode penelitian yang digunakan adalah metode penelitian kualitatif dengan pendekatan eksegesis. Berdasarkan hasil penelitian dapat disimpulkan terdapat dampak positif yang begitu besar dalam pelayanan Diakonia gereja kepada jemaat sehingga membuat pertumbuhan secara kuantitas dan kualitas sampai saat ini. Yang berakar dari pelayanan Diakonia yang dilakukan dengan kunjungan rumah tangga terhadap jemaat yang sakit, jemaat yang berduka dan jemaat yang memiliki masalah-masalah dalam keluarga. Implikasinya, jika pelayanan gereja khususnya Diakonia dilaksanakan dengan baik akan menghasilkan jemaat secara kualitas, kuantitas dan organic yang baik. Dan gereja akan memiliki jemaat yang takut akan Allah dan patuh terhadap Firman Allah.Kata kunci: mandat rasul paulus, tindakan diakonia, kontribusi bagi umat